Synergistic Effects of FGF-18 and TGF-β3 on the Chondrogenesis of Human Adipose-Derived Mesenchymal Stem Cells in the Pellet Culture - Liangjie Huang; Lingxian Yi; Chunli Zhang; Ying He; Liangliang Zhou; Yan Liu; Long Qian; Shuxun Hou; Tujun Weng (Stem Cells International)
Cell-based therapy serves as an effective way for cartilage repair. Compared with a limited source of autologous chondrocytes, adipose-derived stem cells (ADSCs) are proposed as an attractive cell source for cartilage regeneration. How to drive chondrogenic differentiation of ADSCs efficiently remains to be further investigated. TGF-β3 has shown a strong chondrogenic action on ADSCs. Recently, fibroblast growth factor 18 (FGF-18) has gained marked attention due to its anabolic effects on cartilage metabolism, but existing data regarding the role of FGF-18 on the chondrogenic potential of mesenchymal stem cells (MSCs) are conflicting. In addition, whether the combined application of FGF-18 and TGF-β3 would improve the efficiency of the chondrogenic potential of ADSCs has not been thoroughly studied. In the current study, we isolated human ADSCs and characterized the expression of their surface antigens. Also, we evaluated the chondrogenic potential of FGF-18 on ADSCs using an in vitro pellet model by measuring glycosaminoglycan (GAG) content, collagen level, histologic appearance, and expression of cartilage-related genes. We found that FGF-18, similarly to TGF-β3, had a positive impact on chondrogenic differentiation and matrix deposition when presented throughout the culture period. More importantly, we observed synergistic effects of FGF-18 and TGF-β3 on the chondrogenic differentiation of ADSCs in the in vitro pellet model. Our results provide critical information on the therapeutic use of ADSCs with the help of FGF-18 and TGF-β3 for cartilage regeneration.